(untitled) (Yearbook - Faculty of Economics, 2018)
Human resources in public health system have an essential meaning for improvement in economic growth as well as for quality in life. Human resources should be in accordance with the goals and other resources in a country. When we talk about human resources in public health system we mean ‘‘for all people engage in action whose primary aim is promoting health’‘. In this process, the essence is simple ‘‘through adequate work force we can get quality health care’‘.